Supramolecular dendrimers self-assembled from dendritic fullerene ligands and a homotritopic Hamilton receptor - Hager, Kristine; Hartnagel, Uwe; Hirsch, Andreas (European Journal of Organic Chemistry, 2007)
Supramolecular dendrimers resulting from the self-assembly of a series of dendrofullerens 2a-4b containing a cyanuric acid building block at their focal point with the homotritopic Hamilton receptor 1 were prepared. The 1:3 compositions of the supramolecular dendrimers as well as the association constants K and the cooperativity of binding expressed by Scatchard plots and Hill coefficients n were determined by NMR titration experiments. The most pronounced positive cooperativity was observed for the 1:L complexes with L being first generation dendrons. With the bulky second generation dendrons less stable complexes are formed. © Wiley-VCH Verlag GmbH & Co. KGaA, 2007.